2011
DOI: 10.1002/cncy.20177
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ThinPrep and SurePath liquid‐based cytology and subsequent human papillomavirus DNA testing in China

Abstract: BACKGROUND:Liquid-based cytology (LBC) has been compared with conventional cytology in numer-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
0
29
1
Order By: Relevance
“…Both are considered valid technologies, but SurePath has a slightly higher positive predictive value (PPV). 23,24 Given the low prevalence of cervical abnormality in the study population, the results were adjusted for laboratory. There are other known risk factors for HPV infection and cervical cancer, such as smoking.…”
Section: Covariatesmentioning
confidence: 99%
“…Both are considered valid technologies, but SurePath has a slightly higher positive predictive value (PPV). 23,24 Given the low prevalence of cervical abnormality in the study population, the results were adjusted for laboratory. There are other known risk factors for HPV infection and cervical cancer, such as smoking.…”
Section: Covariatesmentioning
confidence: 99%
“…In addition, we estimated that <5% of samples after completion of the conventional Pap smear and for which we must conduct a search for HPV infection contained <2 ml of residual liquid. In the literature, we find a rate of up to 18.2% [8]. This can be a problem when setting up a systematic screening of HPV associated with conventional cytology (small volumes remaining to research HPV).…”
Section: Discussionmentioning
confidence: 99%
“…With the emerging evidence suggesting that LBC is not superior in disease detection over conventional cytology methods in recently published data, the performance of LBC will undoubtedly be challenged when considering escalating costs in the laboratory [6,10,13,17]. Further, it has been suggested that LBC is equivalent to HPV testing in disease detection and others have advocated for adoption of LBC in terms of a more efficient use of automated screening modalities [18].…”
Section: Discussionmentioning
confidence: 99%
“…Some have shown the relative benefits of LBC, including increased sensitivity, especially for the detection of cervical high-grade squamous intraepithelial lesions (HSIL), and the ability to perform HPV testing on the same specimen. Other studies have reported decreased specificity and lower cost-effectiveness [6,10,13]. Nonetheless, the benefits of LBC over conventional cytology include better specimen preservation and presentation, and a higher number of cells on the slide.…”
Section: Introductionmentioning
confidence: 99%